On the use of wearable sensors as mobility biomarkers in the marketing authorization of new drugs: A regulatory perspective - Viceconti, Marco; Tome, Maria; Dartee, Wilhelmus; Knezevic, Igor; Hernandez Penna, Sabina; Mazzà, Claudia; Caulfield, Brian; Garcia-Aymerich, Judith; Becker, Clemens; Maetzler, Walter; Troosters, Thierry; Sharrack, Basil; et al. (Frontiers in Medicine, 2022)
The loss of mobility is a common trait in multiple health conditions (e.g., Parkinson’s disease) and is associated with reduced quality of life. In this context, being able to monitor mobility continuously and accurately in the real world is important. Today, miniaturized sensors and novel algorithms promise to do so, also in pathological populations. However, before any such methodology can be employed to support the development and testing of new drugs in clinical trials, they need to be qualified by competent regulatory agencies. Nonetheless, to date, only very narrow scoped requests for qualification were successful. In this work, the Mobilise-D Consortium shares its experience with the European Medicines Agency, summarizing the requests for Qualification Advice submitted in October 2019 and June 2020, and the feedback received. Leveraging on this, we propose a refined qualification strategy for the use of digital mobility outcomes as monitoring biomarkers for mobility in drug trials.